If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-94=-1-3(1-6a)
We simplify the equation to the form, which is simple to understand
-94=-1-3(1-6a)
Reorder the terms in parentheses
-94=-1+(-3+18a)
Remove unnecessary parentheses
-94=-1-3+18a
We move all terms containing a to the left and all other terms to the right.
-18a=-1-3+94
We simplify left and right side of the equation.
-18a=+90
We divide both sides of the equation by -018 to get a.
a=-5
| 11+9x=59+37x | | 2b=b-2b | | v-11=28 | | -4-3=9x+20 | | x+64=12 | | -5x-5x= | | 15-3(x+3)=21 | | 7x+17=4x-25 | | 2n-9+3=4n+1 | | 5[1.5(x-1)-6.8]-0.31x=3.7 | | 5ln(4x)=17 | | -6b+9+2b=49 | | 4(-3+x)=6-2x | | 7a^2=32a-16 | | 5+5x-4x= | | 3h-12=33 | | 2x+11=59-8x | | 8r^2-34-9=0 | | 2a-7a=9-6a | | 4(4c-1)-4=13c+7 | | 31+5y-9=17y-14-3y | | x/13=-8 | | 8x-8=9x+8 | | -53+2i=-I+73 | | 4m+t= | | 4m+10=2m-6 | | 6-3x=14-7x | | -5(x-3)+2x=6 | | 14(2f)=7(f-2) | | 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 |